Accuracy of dual-source CT to identify significant coronary artery disease in patients with uncontrolled hypertension presenting with chest pain: Comparison with coronary angiography - Marwan, Mohamed; Pflederer, Tobias; Schepis, Tiziano; Seltmann, Martin; Klinghammer, Lutz; Muschiol, Gerd; Ropers, Dieter; Daniel, Werner; Achenbach, Stephan (International Journal of Cardiovascular Imaging, 2012)
It has been previously reported that the sensitivity and specificity of multislice CT for detecting significant CAD (coronary artery disease) is high. Chest pain is a common presentation in patients with uncontrolled hypertension. We investigated the sensitivity and specificity of Dual-Source CT to detect and rule out significant CAD in patients presenting with uncontrolled hypertension accompanied by chest pain. 260 consecutive patients presenting with acute chest pain in the context of stage 2 hypertension (systolic pressure ≥160 and/or diastolic pressure ≥100) were enrolled in the study. After admission, control of blood pressure and risk stratification, 82 patients were excluded due to renal insufficiency, prior coronary revascularisation or refused participation in the study. 90 further patients with low pre-test probability of CAD were also excluded. 88 remaining patients were subjected to CT coronary angiography using Dual-Source CT (Definition, Siemens Medical Solutions, Forchheim, Germany) within 24 h before invasive coronary angiography. A contrast-enhanced volume dataset was acquired (120 kV, 400 mAs/rot, collimation 2 × 64 × 0.6 mm, retrospective ECG gating). Data sets were evaluated concerning the presence or absence of significant coronary stenoses and validated against invasive coronary angiography. A significant stenosis was assumed if the diameter reduction was ≥50%. 88 patients (mean age 66 ± 11 years, mean heart rate 61 ± 9 bpm) were evaluated regarding the presence or absence of significant CAD (at least one stenosis ≥50% diameter reduction). Mean systolic blood pressure on presentation was 203 ± 20 mmHg and mean diastolic blood pressure was 103 ± 13 mmHg. On a per patient basis, the sensitivity and specificity for Dual-Source CT to detect significant CAD in vessels > 1.5 mm diameter was 100% (36/36, 95% CI 90-100) and 90% (47/52, 95% CI 79-97), respectively with a negative predictive value (NPV) of 100% (47/47, 95% CI 92-100) and a positive predictive value (PPV) of 88% (36/41, 95% CI 74-96). On a per artery basis, 352 vessels were evaluated (left main, left anterior descending, left circumflex and right coronary artery in 88 patients, 12 vessels could not be assessed due to either motion artefacts or heavy calcification and were considered positive for stenoses) with a sensitivity of 84% (54/64, 95% CI 72-95) and specificity of 94% (272/288, 95% CI 88-100); NPV was 96% (272/282, 95% CI 90-100) and PPV was 77% (54/70, 95% CI 62-91). Our study demonstrates high sensitivity, specificity and negative predictive value of Dual- Source CT to detect significant CAD in patients presenting with uncontrolled hypertension accompanied by chest pain. Dual-Source CT angiography may be useful to safely rule out coronary artery stenoses and avoid invasive angiograms in these patients. © Springer Science+Business Media, B.V. 2011.
CRIS-Team Scopus Importer:2023-07-10
Keywords: CT; Stenosis; Uncontrolled hypertension

Accuracy of prospectively ECG-triggered very low-dose coronary dual-source CT angiography using iterative reconstruction for the detection of coronary artery stenosis: comparison with invasive catheterization - Layritz, Christian; Schmid, Julia; Achenbach, Stephan; Ulzheimer, Stefan; Wüst, Wolfgang; May, Matthias; Ropers, Dieter; Klinghammer, Lutz; Daniel, Werner; Pflederer, Tobias; Lell, Michael (European Heart Journal - Cardiovascular Imaging, 2014)
To evaluate the image quality and diagnostic accuracy of very low-dose computed tomography (CT) angiography (CTA) for the evaluation of coronary artery stenosis.Iterative reconstruction (IR) has shown to substantially reduce image noise and hence permit the use of very low-dose data acquisition protocols in coronary CTA.Fifty symptomatic patients with an intermediate likelihood for coronary artery disease underwent coronary CTA (heart rate: 59 ± 5 bpm, prospectively ECG-triggered axial acquisition, 100 kV, 160 mAs, 2 × 128 × 0.6 mm collimation, 60 mL contrast, 6 mL/s) prior to invasive coronary angiography. CTA images were reconstructed using both standard filtered back projection (FBP) and a raw data-based IR algorithm [Sinogram Affirmed Iterative Reconstruction (SAFIRE), Siemens Healthcare]. Subjective image quality (four-point Likert scale from 0 = non-diagnostic to 3 = excellent image quality), image noise, signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), as well as the presence of coronary stenosis >50% were independently determined by two observers.The mean dose-length product was 46.8 ± 3.5 mGy cm (estimated effective dose 0.66 ± 0.05 mSv). IR led to significantly improved objective image quality compared with FBP (image noise: 41 ± 12 vs. 49 ± 11 HU, P < 0.0001; CNR: 16 ± 8 vs. 12 ± 4, P < 0.0001; SNR: 13 ± 7 vs. 10 ± 3, P < 0.0001). Four coronary segments were not evaluable on FBP data, whereas all segments showed diagnostic image quality with IR. To detect significant coronary stenosis, sensitivity, specificity, positive predictive value, and negative predictive value were 69% (11/16), 97% (175/180), 69% (11/16), and 97% (175/180) per vessel with FBP data sets, respectively. With IR data sets, the corresponding values were 81% (13/16), 97% (178/184), 68% (13/19), and 98% (178/181). These differences were not statistically significant (P = 0.617).Raw data-based IR significantly improves image quality in very low-dose prospectively ECG-triggered coronary dual-source CTA when compared with standard reconstruction using FBP.
EVALuna2:11955

Association of CRP receptor polymorphisms with culprit lesion morphology in patients with acute myocardial infarction as first manifestation of coronary artery disease - Raaz-Schrauder, Dorette; Klinghammer, Lutz; Lichtenstern, David; Schlundt, Christian; Achenbach, Stephan (2017)
EVALuna2:36024

Association of systemic inflammation markers with the presence and extent of coronary artery calcification - Raaz-Schrauder, Dorette; Klinghammer, Lutz; Baum, Christina; Frank, Thomas; Lewczuk, Piotr; Achenbach, Stephan; Cicha, Iwona; Stumpf, Christian; Wiltfang, Jens; Kornhuber, Johannes; Daniel, Werner; Garlichs, Christoph (Cytokine, 2012)
Background: Coronary artery calcification (CAC) is a marker for the presence and extent of coronary atherosclerotic plaques and can be detected non-invasively by multi-detector row CT (MDCT). Well known predictors of CAC are age, gender, and the classical atherogenic risk factors. CAC is associated with atherosclerotic plaque burden, but it is still elusive if atherosclerosis-relevant cytokines and chemokines are also associated with CAC. Methods: We conducted a clinical study among 455 consecutive individuals who underwent coronary calcium assessment performed by MDCT. Before MDCT, blood was drawn and subsequently analyzed for 20 different atherosclerosis-relevant cytokines and chemokines using a Luminex-laser-based fluorescence analysis. Results: Using univariate analyses, CAC patients revealed significantly higher levels of the chemokines IP-10 (P=0.047) and eotaxin (P=0.031) as compared to non-CAC patients. In multivariate analyses using common thresholds for calcium burden, the three cytokines interleukin-6 (P=0.028), interleukin-8 (P=0.009), and interleukin-13 (P=0.024) were associated with high coronary calcium levels after adjustment for classical variables and risk factors. Conclusions: In a large group of individuals with atypical chest pain and a low to intermediate likelihood for coronary artery disease elevated plasma levels of IL-6 and reduced levels of IL-8 and IL-13 were predictive for distinct coronary artery calcification. These findings support a specific role of these cytokines in coronary calcification. © 2011 Elsevier Ltd.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Atherosclerosis; Cardiac computed tomography; Coronary calcification; Cytokines; Inflammation

Association of systemic inflammation with epicardial fat and coronary artery calcification - Gauss, Soeren; Klinghammer, Lutz; Steinhoff, Alina; Raaz-Schrauder, Dorette; Achenbach, Stephan; Garlichs, Christoph D.; Marwan, Mohamed (Inflammation Research, 2015)
Increased epicardial fat volume (EFV) has been shown to be associated with coronary atherosclerosis. While it is postulated to be an independent risk factor, a possible mechanism is local or systemic inflammation. We analyzed the relationship between coronary atherosclerosis, quantified by coronary calcium in CT, epicardial fat volume and systemic inflammation.Using non-enhanced dual-source CT, we quantified epicardial fat volume (EFV) and coronary artery calcium (CAC) in 391 patients who underwent coronary computed tomography for suspected coronary artery disease. In addition to traditional risk factors, serum markers of systemic inflammation were measured (IL-1?, IL-2, IL-4, IL-6, IL-7, IL-8, IL-10,IL-12, IL-13, IL-15, IL-17, IFN-?, TNF-?, hs-CRP, GM-CS, G-CSF, MCP-1, MIP-1, Eotaxin and IP-10). In 94 patients follow-up data were obtained after 1.9 ± 0.5 years.The 391 patients had a mean age of 60 ± 10 years, and 69 % were males. Mean EFV was 116 ± 50 mL. Median CAC was 12 (IQR 0; 152). CAC and EFV showed a significant correlation (? = 0.37; P < 0.001). EFV and CAC were significantly correlated with the traditional risk factors like age, male gender, diabetes, smoking and hypertension. With regard to biomarkers, CAC was significantly associated (negatively) to G-CSF and IL-13. EFV (median binned) was significantly associated (positively) with IP-10 (P = 0.002) and MCP-1 (? = 0.037). In follow-up, EFV showed a mean annualized progression of 6 mL (IQR 3; 9) (P < 0.001); CAC progressed by a mean of six Agatston Units (IQR 0; 30). The progression of CAC was significantly correlated with the extent of EFV (P < 0.001) while there was no significant correlation between progression of EFV or CAC with systemic inflammation markers.Epicardial fat volume and the baseline extent as well as progression of coronary atherosclerosis-measured by the calcium score-are significantly correlated. While both baseline EFV and CAC displayed significant correlations with systemic inflammation markers, biomarkers were not predictive of the progression of CAC or EFV.
EVALuna2:12060

Bioresorbable vascular scaffold thrombosis in a consecutive cohort of 550 patients - Tröbs, Monique; Achenbach, Stephan; Röther, Jens; Klinghammer, Lutz; Schlundt, Christian (Catheterization and Cardiovascular Interventions, 2016)
OBJECTIVE: To determine the rate of bioresorbable vascular scaffold (BVS) thrombosis in a large, real-world population. BACKGROUND: There is some concern about device thrombosis after percutaneous coronary intervention (PCI) using BVS. No data have been published for PCI using both BVS and metal stents. METHODS: A cohort of 550 consecutive patients who underwent PCI for stable chest pain or acute coronary syndromes with implantation of at least one BVS (Absorb, Abbott Vascular) was systematically followed up by telephone interview and review of medical charts. Data on device thrombosis were retrospectively analyzed in relationship to clinical and angiographic characteristics. RESULTS: Follow-up was achieved in 533 patients (97%, median follow-up 233 days). A total of 964 BVS were implanted in 645 vessels. In addition, 234 metal stents were implanted in 149 patients, including "hybrid intervention" with the combined use of BVS and stents in the same artery in 122 patients. Documented were 15 definite, 1 probable, and 8 possible cases of device thrombosis (rate of definite/probable device thrombosis: 3.0%). Of these, 6 definite and 6 possible thromboses could be unambiguously attributed to BVS (1.1%), whereas a total of 11 definite, 1 probable, and 8 possible thromboses were potentially attributable to BVS (2.3%). Definite device thrombosis occurred in 7/122 patients with "hybrid intervention" (5.7%). CONCLUSIONS: In a large real-world cohort treated with BVS, the rate of scaffold thrombosis was higher than published for randomized trials. A high rate of thrombosis was observed after combined implantation of BVS and stents within one vessel. © 2016 Wiley Periodicals, Inc.
EVALuna2:33663

CD40/CD154 system and pro-inflammatory cytokines in young healthy male smokers without additional risk factors for atherosclerosis - Garlichs, Christoph; Cicha, Iwona; Raaz-Schrauder, Dorette; Meyer, L.; Stumpf, Christian; Klinghammer, Lutz; Yilmaz, Atilla; Daniel, Werner (Inflammation Research, 2009)
Objective and design:: Atherosclerosis, as an inflammatory disease, is characterized by pathologically altered levels of cytokines. We investigated whether smoking affects the CD40/CD154 system and pro-inflammatory cytokines in young males without other risk factors for atherosclerosis. Subjects:: Young male smokers (n=13) and 14 non-smoking controls were investigated. Methods:: The differences in CD40/CD154 system and serum cytokines between the groups were measured using flow cytometry and ELISA. Results:: In smokers, there was a strong trend (P<0.06) for increased CD40 expression on platelets as compared with non-smokers. However, there were no significant differences in CD40 expression on monocytes or in CD154 expression on platelets and T-cells between smokers and non-smokers. There was a strong trend for increased platelet-monocyte aggregates in smokers (P<0.06). Also, smokers had slightly but not significantly elevated hsCRP and IL-6 levels, and slightly decreased TNF-α and MCP-1. Interestingly, IL-18, a cytokine which has the ability to promote both Th1 and Th2 responses, was significantly decreased in smokers group (P=0.03 vs controls). Conclusions:: In young healthy males, smoking is not associated with dramatic changes in CD40/CD154 system. However, cigarette smoke alters the secreted cytokine profile, leading to significant decrease in systemic IL-18 levels. © 2009 Birkhäuser Verlag, Basel.
CRIS-Team Scopus Importer:2023-07-10
Keywords: CD40/CD154; Cytokines; Interleukin-18; Platelets; Smoking

Chronic development of ischaemic mitral regurgitation during post-infarction remodelling - Klinghammer, Lutz; et al. (Cardiology, 2007)
Keywords: Left-ventricular remodelling; Myocardial infarction; Mitral regurgitation; Prognosis

Comparison of Dual-Source Computed Tomography for the Quantification of the Aortic Valve Area in Patients With Aortic Stenosis Versus Transthoracic Echocardiography and Invasive Hemodynamic Assessment - Ropers, Dieter; Ropers, Ulrike; Marwan, Mohamed; Schepis, Titiano; Pflederer, Tobias; Wechsel, Martin; Klinghammer, Lutz; Flachskampf, Frank A.; Daniel, Werner; Achenbach, Stephan (American Journal of Cardiology, 2009)
We compared the measurements of the aortic valve area (AVA) using dual-source computed tomography (DSCT) in patients with mid to severe aortic stenosis to measurements using transthoracic echocardiography (TTE) and invasive hemodynamic assessment. A total of 50 patients (mean age 73 ± 10 years) with suspected aortic stenosis were included. The computed tomographic data were acquired using DSCT with standardized scan parameters (2 × 64 × 0.6 mm collimation, 330-ms rotation, 120-kV tube voltage, 560 mA/rot tube current). After injection of 35 ml contrast agent (flow rate 5 ml/s), a targeted volume data set, ranging from the top of the leaflets to the infundibulum, was acquired. Ten cross-sectional data sets (slice thickness 1 mm, no overlap, increment 0.6 mm) were reconstructed during systole in 5% increments of the R-R interval. The AVA determined in systole by planimetry was compared to the calculated AVA values using the continuity equation on TTE and the Gorlin formula on catheterization. DSCT allowed the planimetry of the AVA in all patients. The mean AVA using DSCT was 1.16 ± 0.47 cm2 compared to a mean AVA of 1.04 ± 0.45 cm2 using TTE and 1.06 ± 0.45 cm2 using catheterization, with a significant correlation between DSCT/TTE (r = 0.93, p <0.001) and DSCT/cardiac catheterization (r = 0.97, p <0.001). However, DSCT demonstrated a slight, but significant, overestimation of the AVA compared to TTE (+0.12 ± 0.17 cm) and catheterization (+0.10 ± 0.12 cm2). In conclusion, DSCT permits one to assess the AVA with a high-image quality and diagnostic accuracy compared to TTE and invasive determination. © 2009 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10

Comparison of Exo-Seal(®) and Angio-Seal (®) for arterial puncture site closure: A randomized, multicenter, single-blind trial - Ketterle, Johannes; Rittger, Harald; Helmig, Inga; Klinghammer, Lutz; Zimmermann, Stefan; Hohenforst-Schmidt, Wolfgang; Brachmann, Johannes; Nef, Holger; Achenbach, Stephan; Schlundt, Christian (Herz, 2015)
The use of extravascular femoral closure devices in patients undergoing coronary angiography/intervention has not been sufficiently evaluated. We sought to define the impact of an extravascular polyglycolic acid (PGA) plug for the closure of a femoral access site in patients undergoing coronary angiography and/or percutaneous coronary intervention.In this prospective, single-blind, multicenter trial we randomly assigned 319 patients to vessel closure with Angio-Seal(®) or Exo-Seal(®). We hypothesized that the use of an extravascular closure device is not inferior to an anchor/plug-mediated device regarding the occurrence of the composite primary endpoint: hematoma > 5 cm, significant groin bleeding (TIMI major bleed), false aneurysm, and device failure.There was no significant difference in patient baseline characteristics or procedural results. After 24 h the primary endpoint occurred in nine patients (5.6 %) in the Angio-Seal(®) group and in 13 patients (8.2 %) inthe Exo-Seal(®) group (p = 0.38). Hematoma > 5 cm was noted in three patients (1.9 %) receiving Angio-Seal(®) vs. two patients (1.3 %) receiving Exo-Seal(®) (p = 0.99). In one patient (0.6 %) of the Exo-Seal(®) group, TIMI major bleeding occurred, requiring transfusion (p = 0.49). There were four (2.5 %) false aneurysms found in patients treated with Angio-Seal(®) and two (1.3 %) in patients treated with Exo-Seal(®) (p = 0.68). There was a trend for a higher incidence of device failure in the Exo-Seal(®) group (1.2 vs. 5.2 %, p = 0.06). At telephone interview after 30 days, there was no significant difference found regarding the events readmission with surgery of puncture site, infection, bleeding, hematoma, or pain.In the present study, there were no significant differences found regarding the occurrence of hematoma > 5 cm, major bleeding, false aneurysm, and device failure between Angio-Seal(®) and Exo-Seal(®) 24 h after device implantation.
EVALuna2:12086

Comparison of intracoronary versus intravenous administration of adenosine for measurement of coronary fractional flow reserve - Schlundt, Christian; Bietau, Christian; Klinghammer, Lutz; Wiedemann, Ricarda; Rittger, Harald; Ludwig, Josef; Achenbach, Stephan (Circulation: Cardiovascular Interventions, 2015)
Measurement of fractional flow reserve (FFR) constitutes the current gold standard to evaluate the hemodynamic significance of coronary stenoses. Limited data validate the intracoronary application of adenosine against standard intravenous infusion. We systematically compared FFR measurements during intracoronary and intravenous application of adenosine about agreement and reproducibility.We included 114 patients with an intermediate degree of stenosis in coronary angiography. Two FFR measurements were performed during intracoronary bolus injection (40 ?g for the right and 80 ?g for the left coronary artery, FFRic), and 2 FFR measurements during continuous intravenous infusion of adenosine (140 ?g/kg per minute, FFRiv). FFR value, the time to reach FFR and patient discomfort (on a subjective scale from 0 for no symptoms to 5 for maximal discomfort) were recorded for each measurement. Mean time to FFR was 100 ± 27 s for continuous intravenous infusion versus 23 ± 14 s for intracoronary bolus administration of adenosine (P < 0.001). Reported discomfort after intracoronary application was significantly lower compared with intravenous adenosine (subjective scale > 0 in 35.1% versus 87.7% of the patients; P < 0.001). Correlation between FFRiv and FFRic was extremely close (r = 0.99; P < 0.001) with no systematic bias in Bland-Altman analysis (bias 0.002 [confidence interval, -0.001 to 0.005]) and low intermethod variability (1.56%). Intramethod variability was not different between intravenous and intracoronary administration (1.47% versus 1.33%; P=0.5).Intracoronary bolus injection of adenosine (40 ?g for the right and 80 ?g for the left coronary artery) yields identical FFR results compared with intravenous infusion (140 ?g/kg per minute), while requiring less time and offering superior patient comfort.
EVALuna2:12052

Contrast volume reduction using third generation dual source computed tomography for the evaluation of patients prior to transcatheter aortic valve implantation - Bittner, Daniel O.; Klinghammer, Lutz; Schuhbaeck, Annika; Hell, Michaela M.; Muschiol, Gerd; Gauss, Soeren; Lell, Michael; Uder, Michael; Hoffmann, Udo; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (European Radiology, 2016)
Chronic renal failure is common in patients referred for transcatheter aortic valve implantation (TAVI). CT angiography is recommended and provides crucial information prior to TAVI. We evaluated the feasibility of a reduced contrast volume protocol for pre-procedural CT imaging.Forty consecutive patients were examined with prospectively ECG-triggered high-pitch spiral acquisition using a novel third-generation dual-source CT system; 38 ml contrast agent was used. Image quality was graded on a visual scale (1-4). Contrast attenuation was measured at the level of the aortic root and at the iliac bifurcation.Mean patient age was 82 ± 6 years (23 males; 58 %). Mean attenuation/average image quality was 285 ± 60 HU/1.5 at the aortic annulus compared to 289 ± 74 HU/1.8 at the iliac bifurcation (p = 0.77/p = 0.29). Mean estimated effective radiation dose was 2.9 ± 0.3 mSv. A repeat acquisition was necessary in one patient due to image quality. Out of the 35 patients who underwent TAVI, 31 (89 %) patients had no or mild aortic regurgitation. Thirty-two (91 %) patients were discharged successfully.Pre-procedural CTA with a total of 38 ml contrast volume is feasible and clinically useful, using third-generation dual-source CT, allowing comprehensive imaging for procedural success.o Reduction of contrast agent volume is crucial in patients with chronic renal failure. o Novel third-generation computed tomography helps to reduce contrast agent volume. o Pre-procedural CT allows comprehensive imaging for procedural success before heart valve implantation. o A low-contrast CT protocol is feasible for pre-procedural TAVI planning.
EVALuna2:14600

CT-based analysis of pericoronary adipose tissue density: Relation to cardiovascular risk factors and epicardial adipose tissue volume - Hell, Michaela M.; Achenbach, Stephan; Schuhbaeck, Annika; Klinghammer, Lutz; May, Matthias; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2016)
Pericoronary adipose tissue (PCAT) can promote atherosclerosis. Metabolically active and inactive PCAT may display different CT densities. However, CT density could be influenced by partial volume effects and image interpolation.To investigate whether PCAT density values in CT displays differences that are larger than those attributable to interpolation and partial volume effects, which would manifest themselves through the relationship between PCAT density and distance from the contrast-enhanced coronary lumen.PCAT density analysis was performed (417 non-atherosclerotic segments, 63 patients) using dual-source CT with a threshold-based measurement method. Changes in PCAT density values depending on distance from the contrast-enhanced coronary lumen and the influence of cardiovascular risk profile were analyzed.Mean PCAT density was -78.1 ± 5.6 HU. PCAT density decreased from proximal to distal segments in the LAD (-78.0 ± 7.3 vs. -82.4 ± 7.7 HU; p < 0.001). PCAT density was higher close to the lumen compared to more peripheral locations (-76.0 ± 6.7 vs. -78.5 ± 5.4 HU; p < 0.001). Decreasing PCAT density was significantly associated with higher epicardial adipose tissue (EAT) volume and body mass index. There was a trend of lower PCAT values with a family history of coronary artery disease.CT-measured attenuation of PCAT is influenced by EAT volume and body mass index. A decrease of PCAT attenuation with increasing distance from the vessel and from proximal to distal segments may suggest variations in CT density of PCAT due to partial volume effects and image interpolation rather than solely due to differences in tissue composition or metabolic activity.
EVALuna2:12033

Data Structure, Management and Transmission. In: TEMOS - Telemedical Emergency Management on Board the International Space Station. Interdisciplinary Study between Johannes Gutenberg-University Mainz, University Erlangen, International Space University Strasbourg and Russian Society of Telemedicine; 50 WB 0148 DLR Final report (163p).p42-67. - Klinghammer, Lutz; Stolyar, Valery; Atkov, Oleg Jurewitsch; Maurer, J; Schäfer, Michael; Khan, Martin; Helou, L; Vollmer, J; Graf, J; Comtesse, R; Mann, Wolf (2004)
Keywords: Telemedicine; Expert Systems; ISS; Space Medicine; Cardiology

Determination of stenotic mitral valve area: New, old, and gold standards - Flachskampf, Frank A.; Klinghammer, Lutz (European Journal of Echocardiography, 2008)

Direct coronary stenting versus predilatation followed by stent placement - Klinghammer, Lutz; et al. (American Journal of Cardiology, 2002)

Early repolarization, left ventricular diastolic function, and left atrial size in professional soccer players - Wilhelm, Matthias; Brem, Matthias; Rost, Christian; Klinghammer, Lutz; Hennig, Friedrich; Daniel, Werner; Flachskampf, Frank (American Journal of Cardiology, 2010)
Recent data have suggested a relation among long-term endurance sport practice, left atrial remodeling, and atrial fibrillation. We investigated the influence of an increased vagal tone, represented by the early repolarization (ER) pattern, on diastolic function and left atrial size in professional soccer players. Fifty-four consecutive athletes underwent electrocardiography, echocardiography, and exercise testing as part of their preparticipation screening. Athletes were divided into 2 groups according to presence or absence of an ER pattern, defined as a ST-segment elevation at the J-point (STE) <0.1 mm in 2 leads. For linear comparisons average STE was calculated. Mean age was 24 ± 4 years. Twenty-five athletes (46%) showed an ER pattern. Athletes with an ER pattern had a significant lower heart rate (54 ± 9 vs 62 ± 11 beats/min, p = 0.024), an increased E/e′ ratio (6.1 ± 1.2 vs 5.1 ± 1.0, p = 0.002), and larger volumes of the left atrium (25.6 ± 7.3 vs 21.8 ± 5.0 ml/m2, p = 0.031) compared to athletes without an ER pattern. There were no significant differences concerning maximum workload, left ventricular dimensions, and systolic function. Univariate regression analysis revealed significant correlations among age, STE, and left atrial volume. In a stepwise multivariate regression analysis age, STE and e′ contributed independently to left atrial size (r = 0.659, p <0.001). In conclusion, athletes with an ER pattern had an increased E/e′ ratio, reflecting a higher left atrial filling pressure, contributing to left atrial remodeling over time. © 2010 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10

Epicardial fat and coronary artery calcification in patients on long-term hemodialysis - Gauss, Soeren; Klinghammer, Lutz; Jahn, Daniela; Schuhbaeck, Annika; Achenbach, Stephan; Marwan, Mohamed (Journal of Computer Assisted Tomography, 2014)
Introduction: Recent studies have shown a significant correlation between increased epicardial fat volume (EFV) andmortality, coronary artery disease events, andmeasures of coronary atherosclerotic burden, for example, coronary calcium. Patients with chronic kidney disease on hemodialysis have an increased prevalence of coronary atherosclerosis and coronary calcium. The mechanisms underlying both may differ from patients with normal kidney function. Only limited data are available on the relationship between epicardial fat and coronary calcium in these patients.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac CT; Coronary artery calcification; Dialysis; Epicardial fat

European Association of Echocardiography recommendations for assessment of valvular regurgitation: A correction - Flachskampf, Frank A.; Klinghammer, Lutz (European Journal of Echocardiography, 2010)
CRIS-Team Scopus Importer:2023-07-10

FcγRIIa genotype is associated with acute coronary syndromes as first manifestation of coronary artery disease - Raaz, Dorette; Herrmann, Martin; Ekici, Arif Bülent; Klinghammer, Lutz; Lausen, Berthold; Voll, Reinhard E.; Leusen, Jeanette H.W.; van de Winkel, Jan G.J.; Daniel, Werner; Reis, André; Garlichs, Christoph (Atherosclerosis, 2009)
Objective: Identification of clinically relevant determinants for acute coronary syndromes (ACS) promises reduction of ACS-associated mortality. C-reactive protein (CRP) has proved to be useful identifying people at risk for cardiovascular events. However, it is unknown whether genetic variants at Fcγ receptor IIa (FcγRIIa), the main receptor for CRP, are involved in CRP-related cardiovascular risk. We evaluated the potential impact of FcγRIIa through a genetic association study in patients with ACS. Methods and results: We conducted a genetic association study among 701 consecutive patients with first event of ACS compared to 467 patients with stable angina pectoris. All patients were genotyped for a frequent functional variant at position 131 of the mature FcγRIIa, where the arginine (R) allele results in an increased signal transduction upon CRP binding. In our study, the R/R131 genotype was significantly associated with ACS as the first manifestation of coronary artery disease (P = 1.2 × 10-9, odds ratio 2.86, 95% CI: 2.06-3.99) compared to the non-R/R131 genotype. Conclusions: Our data show a genetic association of the FcγRIIa R/R131 genotype with a more frequent occurrence of ACS as the first manifestation of coronary artery disease, probably mediated via its interaction with CRP. Genotyping of this FcγRIIa variant could help to improve risk stratification in the course of coronary disease in the future. © 2009 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Acute coronary syndrome; Fcγ receptor IIa; Gene polymorphism; Inflammation

Histamine in atrial fibrillation (AF)–is there any connection? Results from an unselected population - Layritz, C. M.; Hagel, Alexander; Graf, V.; Reiser, C.; Klinghammer, Lutz; Ropers, Dieter; Achenbach, Susanne; Raithel, M. (International Journal of Cardiology, 2014)
EVALuna2:1903

Impact of telmisartan on the inflammatory state in patients with coronary atherosclerosis - Influence on IP-10, TNF-α and MCP-1 - Klinghammer, Lutz; Urschel, Katharina; Cicha, Iwona; Lewczuk, Piotr; Raaz-Schrauder, Dorette; Achenbach, Stephan; Garlichs, Christoph (Cytokine, 2013)
Background: Hypertension is one of the most prominent risk factors for coronary artery disease (CAD). Treatment of hypertension is therefore important for reducing cardiovascular events and the progression of atherosclerosis. Several treatment strategies are common in clinical practice for example the use of ACE-blockers or angiotensin receptor II blockers (ARBs), so called sartans. Telmisartan, belonging to the class of ARBs, was shown to exert anti-inflammatory effects besides the blood pressure lowering. Methods: In this work, two separate substudy groups of hypertensives were compared. 16 patients with arterial hypertension have been treated with telmisartan (initial 40. mg Kinzalmono®) for 7.3±4.4 months. The telmisartan group was compared to a matched control group including 31 hypertensive patients without telmisartan treatment with a follow up period of 1.9±0.5 years. Serum samples from the beginning and the end of follow up were analyzed with Luminex® technology for 26 cytokines and chemokines. The baseline scores of coronary artery calcification (CAC) were gathered by multislice detector computer tomography. Results: After 7. months of telmisartan treatment and 2. years in control patients most of the measured analytes did not change significantly. MCP-1 (P=0.001; P<0.001) was increased significantly in both telmisartan and control group. The relative decrease in IP-10 and TNF-α levels was observed in telmisartan group, as opposed to the increase in control (telmisartan vs. control P=0.048; P=0.01). No linear rank-correlation between measured analytes and the initial CAC was found. Conclusion: Telmisartan reduced blood pressure in patients with atherosclerosis and arterial hypertension within a short time period, whereas the inflammatory status of these patients remained largely unchanged. An involvement of telmisartan in the regulation of inflammatory and anti-inflammatory mediators in the context of CAD and CAC is possible, but cannot clearly be assumed based on the present findings. © 2013.
CRIS-Team Scopus Importer:2023-03-08
Keywords: %Δa; Δ; Δa; Atherosclerosis; CAC; Chemokines; Cytokines; Risk factors; Telmisartan

Increased prolactin in acute coronary syndromes as putative co-activator of ADP-stimulated P-selectin expression - Klinghammer, Lutz; et al. (Hormone and Metabolic Research, 2006)
Keywords: Angina pectoris; Coronary artery disease; Acute myocardial infarction; Platelets; Hormones; Leptin

Influence of Cardiovascular Risk Factors on the Prevalence of Coronary Atherosclerosis in Patients with Angiographically Normal Coronary Arteries - Bittner, Daniel O.; Klinghammer, Lutz; Schmid, Jasmin; Layritz, Christian; Hoffmann, Udo; Achenbach, Stephan; Pflederer, Tobias; Marwan, Mohamed (Academic Radiology, 2017)
RATIONALE AND OBJECTIVES: Cardiovascular (CV) disease is predominately influenced by CV risk factors and coronary computed tomography angiography (CTA) is capable of detecting early-stage coronary artery disease. We sought to determine the influence of CV risk factors on the prevalence of nonobstructive atherosclerosis in patients with normal-appearing coronary arteries in invasive coronary angiography (ICA). MATERIALS AND METHODS: In this retrospective analysis, we included 60 consecutive symptomatic patients, having undergone ICA and coronary CTA. Coronary dual source CTA was performed using electrocardiogram-triggered retrospective gated image acquisition at 40%-70% of RR interval (tube voltage 100-120 kV, tube current time product 320-440 mAs, 60 mL contrast, and flow rate 6 mL/s). RESULTS: Out of 60 patients (32 men, mean age 61 ± 11 years) with a normal coronary artery appearance in ICA, 45 (75%) patients showed atherosclerotic plaque in CTA. Plaque was present in 14 of 60 (23%) left main, 41 of 60 (68%) left anterior descending, 21 of 60 (35%) circumflex coronary arteries, and 24 of 60 (40%) right coronary arteries. More than 15% of all coronary artery segments showed detectable plaques. Interobserver agreement ranged from good to very good on a per-patient, per-vessel, and per-segment level. Patients with presence of plaque were significantly older (P = 0.005) and showed higher incidence of arterial hypertension (P = 0.019) as compared to individuals without coronary plaque in dual source computed tomography. CONCLUSIONS: The prevalence of coronary atherosclerosis by CTA is substantial in symptomatic patients with normal invasive coronary angiogram. Hypertension and older age significantly influence the prevalence of atherosclerotic plaque and highlight the importance of risk-modifying therapy.
EVALuna:33640

Influence of ultrasound operating parameters on ultrasound-induced thrombolysis in vitro - Klinghammer, Lutz; et al. (Ultrasound in Medicine and Biology, 2005)
Keywords: Cavitation; Operating parameters; Ultrasound thrombolysis

Interobserver variability of CT angiography for evaluation of aortic annulus dimensions prior to transcatheter aortic valve implantation (TAVI) - Schmidkonz, Christian; Marwan, M.; Klinghammer, Lutz; Mitschke, M.; Schuhbaeck, A.; Lell, Michael; Achenbach, Susanne; Pflederer, T.; Arnold, Martin (European Journal of Radiology, 2014)
Assessment of aortic annulus dimensions prior to transcatheter aortic valve implantation (TAVI) is crucial for accurate prosthesis sizing in order to avoid prosthesis-annulus-mismatch possibly resulting in complications like valve dislodgement, paravalvular regurgitation or annulus rupture. Contrast-enhanced multidetector computed tomography allows 3-dimensional assessment of aortic annulus dimensions. Only limited data exist about its interobserver variability.In 100 consecutive patients with symptomatic severe aortic stenosis (51 male, BMI 27±5kg/m(2), age 81±7 years, heart rate 72±15bpm, Logistic Euroscore 31±14%, STS-Score 7±4%), pre-interventional aortic annulus assessment was performed by dual source computed tomography (collimation 2×128×0.6mm, high pitch spiral data acquisition mode, 40-60ml contrast agents, radiation dose 3.5±0.9mSv). The following aortic annulus characteristics were determined by three independent observers: aortic annulus maximum, minimum and mean diameters (Dmax, Dmin, Dmean), eccentricity index (EI), effective aortic annulus diameter according to its circumference (Dcirc), effective aortic annulus diameter according to its area (Darea), distance from the aortic annulus plane to the left (LCA) and right coronary artery (RCA) ostia, maximum (DmaxAR) and minimum aortic root diameter (DminAR), maximum (DmaxSTJ) and minimum diameter of the sinotubular junction (DminSTJ). Subsequently, interobserver variabilities were assessed.Correlation between the three observers showed moderate to close agreement (between r=0.67 and r=0.97, all p<0.001). Mean differences (SE) between the three observers ranged from 0.07 (0.06)mm to 0.24 (0.07)mm for assessing the mean AA diameter (Dmean), from 0.28 (0.04)mm to 0.60 (0.06)mm for determining the effective AA diameter derived from the annulus area (Darea) and from 0.03 (0.07)mm to 0.07 (0.11)mm derived from the AA perimeter (Dcirc). For measurements of LCA and RCA distances to the AA level, mean interobserver differences (SE) ranged from 0.36 (0.07)mm to 0.76 (0.09)mm and from 0.15 (0.06)mm to 0.45 (0.11)mm.Computed tomography provides reproducible measurements of the aortic annulus and root geometry in patients scheduled for TAVI. The perimeter-derived aortic annulus diameter shows the lowest interobserver differences. Interobserver variabilities in prosthesis size recommendation were further reduced, if all three sizing methods were considered and stated as a "consensus result".
EVALuna2:11956

Invasive hemodynamic characteristics of low gradient severe aortic stenosis despite preserved ejection fraction - Lauten, Juliane; Rost, Christian; Breithardt, Ole A.; Seligmann, Christian; Klinghammer, Lutz; Daniel, Werner; Flachskampf, Frank A. (Journal of the American College of Cardiology, 2013)
Objectives: The study sought to compare echocardiographic with invasive hemodynamic data in patients with "paradoxic" aortic stenosis and in patients with conventionally defined severe aortic stenosis. Background: Controversy exists whether low gradient severe aortic stenosis despite preserved ejection fraction ("paradoxic" aortic stenosis; aortic valve area <1 cm2, mean gradient <40 mm Hg, ejection fraction >50%), which has been mainly diagnosed by echocardiography (echo), may be largely due to mistakes in echocardiographic measurements. Methods: We compared echocardiographic and invasive hemodynamic data from 58 patients (43% male, mean age 77 ± 5 years) with "paradoxic" aortic stenosis. Data of 22 patients (45% male, mean age 73 ± 7 years) with conventionally defined severe aortic stenosis area (aortic valve area ≤1 cm2, mean gradient >40 mm Hg, ejection fraction ≥50%) were also analyzed. Results: In patients with "paradoxic" aortic stenosis, orifice area by echo (0.80 ± 0.15 cm2) and catheterization showed modest agreement, whether stroke volume was measured by oxymetry (0.69 ± 0.16 cm 2, bias 0.14 ± 0.17 cm2), or by thermodilution (0.85 ± 0.19 cm2, bias -0.03 ± 0.19 cm2). Mean systolic gradients were very similar (32 ± 7 mm Hg vs. 31 ± 6 mm Hg; bias -0.08 ± 7.8 mm Hg). In comparison, in patients with conventionally defined severe aortic stenosis, orifice area by echo was 0.72 ± 0.17 cm2 and by catheterization 0.51 ± 0.15 cm 2 (oxymetry) and 0.68 ± 0.21 cm2 (thermodilution), respectively, and mean systolic gradient 51 ± 10 mm Hg and 55 ± 8 mm Hg, respectively. Ejection fractions did not differ significantly in both groups. Ascending aortic diameter was significantly smaller in the "paradoxic" aortic stenosis group than in patients with conventionally defined severe aortic stenosis (28 ± 5 mm vs. 31 ± 5 mm), and energy loss index was significantly larger (0.51 ± 0.12 cm 2/m2 vs. 0.42 ± 0.09 cm2/m2, respectively). Heart rate and mean blood pressure during echo and catheterization were not significantly different. Conclusions: Occurrence of low gradient severe aortic stenosis despite preserved ejection fraction was confirmed by invasive hemodynamics and was not the result of a systematic bias in the echo calculation of aortic orifice area. © 2013 American College of Cardiology Foundation.
CRIS-Team Scopus Importer:2023-07-10
Keywords: aortic stenosis; cardiac catherization; echocardiography

Low-dose dual-source CT angiography with iterative reconstruction for coronary artery stent evaluation - Eisentopf, Jasmin; Achenbach, Stephan; Ulzheimer, Stefan; Layritz, Christian; Wüst, Wolfgang; May, Matthias; Lell, Michael; Ropers, Dieter; Klinghammer, Lutz; Daniel, Werner; Pflederer, Tobias (Journal of the American College of Cardiology : Cardiovascular imaging, 2013)
Objectives: The purpose of this study was to evaluate the image quality and diagnostic accuracy of very low-dose, dual-source computed tomography (DSCT) angiography for the evaluation of coronary stents. Background: Iterative reconstruction (IR) leads to substantial reduction of image noise and hence permits the use of very low-dose data acquisition protocols in coronary computed tomography angiography. Methods: Fifty symptomatic patients with 87 coronary stents (diameter 3.0 ± 0.4 mm) underwent coronary DSCT angiography (heart rate, 60 ± 6 beats/min; prospectively electrocardiography-triggered axial acquisition; 80 kV, 165 mA, 2 × 128 × 0.6-mm collimation; 60 ml of contrast at 6 ml/s) before invasive coronary angiography. DSCT images were reconstructed using both standard filtered back projection and a raw data-based IR algorithm (SAFIRE, Siemens Healthcare, Forchheim, Germany). Subjective image quality (4-point scale from 0 [nondiagnostic] to 3 [excellent image quality]), image noise, contrast-to-noise ratio as well as the presence of in-stent stenosis >50% were independently determined by 2 observers. Results: The median dose-length product was 23.0 (22.0; 23.0) mGy · cm (median estimated effective dose of 0.32 [0.31; 0.32] mSv). IR led to significantly improved image quality compared with filtered back projection (image quality score, 1.8 ± 0.6 vs. 1.5 ± 0.5, p < 0.05; image noise, 70 Hounsfield units [62; 80 Hounsfield units] vs. 96 Hounsfield units [82; 113 Hounsfield units], p < 0.001; contrast-to-noise ratio, 11.0 [9.6; 12.4] vs. 8.0 [6.2; 9.3], p < 0.001). To detect significant coronary stenosis in filtered back projection reconstructions, the sensitivity, specificity, positive predictive value, and negative predictive value were 97% (32 of 33), 53% (9 of 17), 80% (32 of 40), and 90% (9 of 10) per patient, respectively; 89% (43 of 48), 79% (120 of 152), 57% (42 of 74), and 96% (121 of 126) per vessel, respectively; and 85% (12 of 14), 69% (51 of 73), 32% (11 of 34), and 96% (51 of 53) per stent, respectively. In reconstructions obtained by IR, the corresponding values were 100% (33 of 33), 65% (11 of 17), 85% (33 of 39), and 100% (11 of 11) per patient, respectively; 96% (46 of 48), 84% (129 of 152), 66% (47 of 71), and 98% (127 of 129) per vessel, respectively; and 100% (14 of 14), 75% (55 of 73), 44% (14 of 32), and 100% (55 of 55) per stent, respectively. These differences were not significant. Conclusions: In selected patients, prospectively electrocardiography-triggered image acquisition with 80-kV tube voltage and low current in combination with IR permits the evaluation of patients with implanted coronary artery stents with reasonable diagnostic accuracy at very low radiation exposure. © 2013 American College of Cardiology Foundation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: coronary CT angiography; iterative reconstruction; low dose; stent

Mild therapeutic hypothermia after out-of-hospital cardiac arrest complicating ST-elevation myocardial infarction: Long-term results in clinical practice - Zimmermann, Stefan; Flachskampf, Frank A.; Schneider, Reinhard; Dechant, Katharina; Alff, Anna; Klinghammer, Lutz; Rittger, Harald; Achenbach, Stephan (Clinical Cardiology, 2013)
Background Recently, mild therapeutic hypothermia (MTH) has been integrated into the European resuscitation guidelines to improve outcomes after out-of-hospital cardiac arrest (OHCA). Data on long-term results are limited, especially in patients with acute ST-elevation myocardial infarction (STEMI). Hypothesis Invasive MTH influences long-term prognosis after OHCA due to STEMI. Methods We analyzed 48 patients who underwent emergency coronary angiography for STEMI after witnessed OHCA. In 24 consecutive patients, MTH was performed via intravascular cooling (CoolGard System, 34°C maintained for 24 hours) after initialization by rapid infusion of cold saline. Clinical, procedural, and mortality data were compared to 24 historical controls. Neurological recovery was assessed using the Cerebral Performance Category score (CPC) at 30-day and 1-year follow-up. Results Median time delay until arrival of emergency medical service was 6 minutes (MTH group) vs 6.5 minutes (controls) (P = 0.16). Initial rhythm was ventricular fibrillation in 75% vs 66.7% (P = 0.75). There were no differences regarding baseline characteristics, angiographic findings, and success of cardiac catheterization procedures. MTH was not associated with a higher frequency of bleeding complications or of pneumonia. Thirty-day mortality was 33.3% in both groups. One-year mortality was 37.5% (MTH group) vs 50% (controls) (P = 0.56). At 1 year, favorable neurological outcome (CPC ≤2) was significantly more frequent in the MTH group (58.3% vs 20.8%, P = 0.017). Multivariate analysis identified MTH as independent predictor of favorable neurological outcome (P < 0.02, odds ratio: 12.73). Conclusions MTH via intravascular cooling improves neurological long-term prognosis after OHCA due to STEMI and is safe in clinical practice. © 2013 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-03-08

Outcomes of contemporary interventional therapy of ST elevation infarction in patients older than 75 years - Zimmermann, Stefan; Ruthrof, Susanne; Nowak, Kathrin; Klinghammer, Lutz; Ludwig, Josef; Daniel, Werner; Flachskampf, Frank A. (Clinical Cardiology, 2009)
Background: Data on contemporary real-world outcomes of interventional revascularization in patients ≥75 y of age with ST elevation infarction (STEMI) are limited. Methods: We analyzed all 504 consecutive patients who underwent angiography for acute STEMI between 1999 and 2005 at our center, and followed them up over one year. Outcomes in patients ≥75 y of age were compared with younger patients. Results: Patients ≥75 y of age (n = 115) were majority females (55% versus 21%, p<0.001), more cases of diabetes (42% versus 27%, p = 0.004), hypertension (78% versus 65%, p = 0.03) and a history of coronary events (25% versus 15%, p = 0.002). Younger patients were more often smokers (63% versus 30%, p<0.001). After coronary angiography patients ≥75 y of age underwent less frequent intervention (PCI; 84% versus 93%, p = 0.01). However, if PCI was performed, technical success rates were similar to younger patients (84% versus 86%). The 30-d mortality was 13% versus 6.4% (p = 0.03), but after successful PCI, the 30-d mortality rate was not significantly higher in old patients (7.4% versus 3.9%, p = 0.23). Bleeding complications were very low in both age groups if the radial access route was chosen. Multivariate predictors of 30-d mortality were cardiogenic shock/survived cardiac arrest, ejection fraction < 30%, conservative treatment or unsuccessful PCI (OR 3.01), renal insufficiency, diabetes, and age. One-y mortality was higher in the elderly (24.3% versus 9.9%, p<0.001). Among 30-d-survivors, only multivessel disease and age were multivariate predictors of 1-ymortality. Conclusion: Patients ≥75 y of age benefit from PCI in STEMI, and failed or unattempted PCI worsens prognosis in the old as well as in younger patients. © 2009 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Acute cardiac care; Acute coronary syndrome; Percutaneous intervention

Out-of-hospital cardiac arrest and percutaneous coronary intervention for ST-elevation myocardial infarction: Long-term survival and neurological outcome - Zimmermann, Stefan; Flachskampf, Frank A.; Alff, Anna; Schneider, Reinhard; Dechant, Katharina; Klinghammer, Lutz; Stumpf, Christian; Zopf, Yurdagül; Loehr, Thomas; Brand, Georg; Ludwig, Josef; Daniel, Werner; et al. (International Journal of Cardiology, 2013)
Background: Predictors of long-term outcome after ST-elevation myocardial infarction (STEMI) complicated by out-of-hospital cardiac arrest (OHCA) are incompletely understood, including the influence of successful coronary reperfusion. Methods: We analysed clinical and procedural data as well as 1-year outcome of 72 consecutive patients who underwent primary coronary intervention (PCI) after witnessed OHCA and STEMI and compared the results with 695 patients with STEMI and PCI, but without OHCA. Neurological recovery after OHCA was assessed using the Cerebral Performance Category (CPC) scale. Results: PCI was successful in 83.3% after OHCA vs. 84.3% in the non-OHCA group (p = 0.87). One-year mortality was 34.7% vs. 9.5% (p < 0.001). 58.3% of the OHCA-patients showed complete neurological recovery (CPC 1) or moderate neurological disability (CPC 2). Another 6.9% showed severe cerebral disability (CPC 3) or permanent vegetative status (CPC 4). Delay from collapse until start of Advanced Cardiopulmonary Life Support (ACLS) was shorter for survivors with CPC status ≤ 2 (median 1 min, range 0-11 min) compared to non-survivors or survivors with CPC status > 2 (median 8 min, range 0-13 min), p < 0.0001. Age-adjusted multivariate analysis identified 'unsuccessful PCI', 'vasopressors on admission' and 'start of ACLS after > 6 min' as independent predictors of negative long-term outcome (death or CPC > 2). Conclusions: Mortality is high in patients with STEMI complicated by OHCA - even though PCI was performed with the same success rate as in patients without OHCA. The majority of survivors had favourable neurological outcomes at 1 year, especially if advanced life support had been started within ≤ 6 min and PCI was successful. © 2011 Elsevier Ireland Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac arrest; Outcome; Primary coronary intervention; Prognosis; Resuscitation; ST-elevation myocardial infarction

Patients with acute coronary syndromes express enhanced CD40 ligand/CD 154 on platelets - Klinghammer, Lutz; et al. (Heart, 2001)
UnivIS-Import:2015-03-09:Pub.2001.med.MKIPI.MKIPLA.patien
Keywords: Acute coronary syndromes; Platelets; Unstable angina; CD40L/CD 154

Patients with atypical chest pain show associations with pro-atherogenic cytokines and levels of sRANKL and OPG - Raaz-Schrauder, D.; Stumpf, Christian; Schrauder, Michael G.; Lewczuk, Piotr; Dietel, B.; Garlichs, Christoph; Achenbach, Stephan; Klinghammer, Lutz (2016)
EVALuna2:33388

Patients with unstable angina pectoris show an increased frequency of the Fc gamma RIIa R131 allele - Raaz-Schrauder, Dorette; Ekici, Arif Bülent; Munoz, Luis Enrique; Klinghammer, Lutz; Voll, Reinhard E.; Leusen, Jeanette H.W.; Van De Winkel, Jan G.J.; Reis, André; Schett, Georg; Garlichs, Christoph; Herrmann, Martin (Autoimmunity, 2012)
Patients with Systemic Lupus Erythematosus (SLE) carry an increased risk for the development of coronary artery disease (CAD). The R131 allele of the Fc gamma receptor IIa (FcγRIIa) is associated with SLE incidence and disease severity but also with CAD. Compared to stable angina pectoris (SAP) the unstable angina (UAP), as a manifestation of destabilizing CAD, is associated with increased risk of persistent instability, myocardial infarction, and death. Identification of clinically relevant determinants for unstable angina promises reduction of UAP-associated mortality in patients with SLE. We conducted a clinical study among 553 consecutive patients with stable angina pectoris (n 330) and unstable angina pectoris (n 223). All patients were genotyped for a frequent functional variant at position 131 of the mature FcγRIIa. UAP, but not SAP was significantly associated with the R/R131 genotype (P < 0.001). In troponin-negative patients with angina carrying the R/R131 genotype the odds ratio for suffering from UAP was 4.02 (95% confidence interval, 2.526.41) compared to those with non-R/R131 genotypes. In a multivariable analysis, the R/R131 genotype independently predicted the risk for development of UAP in a model adjusted for classical atherogenic risk factors. Our data imply that risk stratification of SLE- and other high risk patients with troponin-negative angina could be significantly improved by FcγRIIa genotyping. © Informa UK, Ltd.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Allele R131; Coronary disease; Fc gamma receptor IIa; SLE; Stable; Unstable angina pectoris

PHENOTYPE OF VULNERABLE ATHEROSCLEROTIC PLAQUES SHOWS STRONG ASSOCIATION WITH SINGLE NUCLEOTIDE POLYMORPHISM ALLELES OF COMMON RISK VARIANTS FOR CORONARY ARTERY DISEASE - Furtmair, R.; Kühn, Charlotte; Koenig, C.; Ekici, Arif Bülent; Klinghammer, Lutz; Achenbach, Stephan; Reis, André; Tauchi, M.; Dietel, B. (2016)
EVALuna2:33679

Plasma levels of sRANKL and OPG are associated with atherogenic cytokines in patients with intermediate cardiovascular risk - Raaz-Schrauder, Dorette; Schrauder, Michael G.; Stumpf, Christian; Lewczuk, Piotr; Kilian, Tobias; Dietel, Barbara; Garlichs, Christoph D.; Schlundt, Christian; Achenbach, Stephan; Klinghammer, Lutz (Heart and Vessels, 2017)
Osteoprotegerin (OPG) and receptor activator of nuclear factor-κB ligand (RANKL) are regulators of bone remodeling, but are also considered to play important roles in coronary artery disease (CAD). This study evaluated potential associations of soluble (s) RANKL and OPG with atherosclerosis-relevant cytokines. Blood was collected from 414 individuals who presented to our hospital with intermediate likelihood for CAD for further examination. Plasma concentrations of total sRANKL, OPG, and 20 cytokines were measured using sandwich-type enzyme-linked immunoassays (ELISAs; OPG and sRANKL) and Luminex laser-based fluorescence analysis and correlated with each other. The plasma levels of interferon-γ (IFN-γ) and the T-helper cell 2 cytokines interleukin-4 (IL-4) and IL-13 showed a positive correlation with sRANKL. The association with sRANKL levels was negative for IFN-γ-induced protein-10 (IP-10) and monocyte chemotactic protein-1 (MCP-1). The strongest independent association with sRANKL in multivariable analyses was found for IFN-γ (positive) and IP-10 (negative), while IL-13 showed a positive and independent association with OPG plasma levels. OPG and sRANKL plasma levels correlate strongly and independently with specific circulating atherosclerosis-related cytokines in patients with intermediate cardiovascular risk.
EVALuna2:33557

Platelet CD40 contributes to enhanced monocyte chemoattractant protein 1 levels in patients with resistant hypertension - Stumpf, Christian; Raaz, Dorette; Klinghammer, Lutz; Schneider, Markus; Schmieder, Roland; Garlichs, Christoph D.; Achenbach, Stephan (European Journal of Clinical Investigation, 2016)
Growing evidence shows that inflammation plays a pivotal role in the pathophysiology of essential hypertension (EH). Although it is acknowledged that target organ damage involves an inflammatory response, most work has focused on the role of macrophages. However, recently, platelets were identified as inducing inflammation partly by releasing cytokines. The goal of our study was to evaluate the role of platelets as inflammatory cells in the pathogenesis of EH.Thirty-nine patients with EH and 30 healthy normotensive controls have been examined. Expression of platelet CD40 was measured by flow cytometry. Serum levels of monocyte chemoattractant protein 1 (MCP-1) and sCD40L were measured via a multiplexing assay. In in vitro experiments, activated platelets were cocultured with human umbilical vein endothelial cells (HUVEC) in the presence and absence of anti-CD154 antibodies. MCP-1 in the supernatants was measured by EIA.Essential hypertension patients showed significantly enhanced MCP-1 levels with highest levels in EH patients with microalbuminuria. EH patients showed increased expression of platelet CD40. In the cell coculture model, activated platelets were able to significantly induce MCP-1 release from HUVEC in a CD40L-dependent manner. EH patients showed elevated sCD40L levels with a positive correlation with MCP-1 levels.Platelets can contribute to enhanced MCP-1 levels in EH. MCP-1 is markedly elevated in serum of EH patients with highest levels in patients with microalbuminuria, one early sign of renal target organ damage. Further studies are required to test whether MCP-1 blocking or antiplatelet strategies may represent new therapeutic options in preventing hypertensive target organ damage.
EVALuna2:3852

Pneumatic external counterpulsation–a new technical perfusion principle Pneumatische externe Gegenpulsation–ein neues perfusionstechnisches Prinzip. - Klinghammer, Lutz; et al. (Biomedizinische Technik, 1998)

Predictive value of the decrease in circulating dendritic cell precursors in stable coronary artery disease - Yilmaz, Atilla; Schaller, Tina; Cicha, Iwona; Altendorf, Regina; Stumpf, Christian; Klinghammer, Lutz; Ludwig, Josef; Daniel, Werner; Garlichs, Christoph (Clinical Science, 2009)
DCs (dendritic cells) are present in atherosclerotic lesions leading to vascular inflammation, and the number of vascular DCs increases during atherosclerosis. Previously, we have shown that the levels of circulating DCPs (DC precursors) are reduced in acute coronary syndromes through vascular recruitment. In the present study, we have investigated whether DCP levels are also reduced in stable CAD (coronary artery disease). The levels of circulating mDCPs (myeloid DCPs), pDCPs (plasmacytoid DCPs) and tDCP (total DCPs) were investigated using flow cytometry in 290 patients with suspected stable CAD. A coronary angiogram was used to evaluate a CAD score for each patient as follows: (i) CAD excluded (n = 57); (ii) early CAD (n = 63); (iii) moderate CAD (n = 85); and (iv) advanced CAD (n = 85). Compared with controls, patients with advanced stable CAD had lower HDL (high-density lipoprotein)-cholesterol (P = 0.03) and higher creatinine (P = 0.003). In advanced CAD, a significant decrease in circulating mDCPs, pDCPs and tDCPs was observed (each P < 0.001). A significant inverse correlation was observed between the CAD score and mDCPs, pDCPs or tDCPs (each P < 0.001). Patients who required percutaneous coronary intervention or coronary artery bypass grafting had less circulating mDCPs, pDCPs and tDCPs than controls (each P < 0.001). Multiple stepwise logistic regression analysis suggested mDCPs, pDCPs and tDCPs as independent predictors of CAD. In conclusion, we have shown that patients with stable CAD have significantly lower levels of circulating DCPs than healthy individuals. Their decrease appears to be an independent predictor of the presence of, and subsequent therapeutic procedure in, stable CAD. © The Authors Journal compilation © 2009 Biochemical Society.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Atherosclerosis; Coronary artery disease; Dendritic cell; Immune system; Inflammation

Predictors of Technical Failure in Transradial Coronary Angiography and Intervention - Tröbs, Monique; Achenbach, Stephan; Plank, Pia Maria; Röther, Jens; Klinghammer, Lutz; Blachutzik, Florian; Schlundt, Christian; Marwan, Mohamed (American Journal of Cardiology, 2017)
Transradial access for coronary angiography and intervention is preferred over the femoral approach but can be technically challenging. Identification of predictors of transradial access failure is important, especially in the context of acute coronary syndromes. We therefore retrospectively analyzed 13,095 consecutive patients (66 ± 12 years, 64% male) in whom transradial access was attempted for coronary angiography or intervention to identify predictors of transradial access failure. Angiograms and patient files were systematically reviewed to analyze patient characteristics associated with failure. Transradial access failure rate was 6.8% (909 of 13,095). Patients with transradial access failure were more frequently female (9.5% vs 5.5%; p <0.001), significantly older (68 ± 12 vs 66 ± 12 years, p <0.001), and had a smaller body surface area (1.89 ± 0.21 vs 1.94 ± 0.2 m2; p <0.001). Transradial failure was not significantly more frequent in ST-elevation myocardial infarction versus other patients (8.1% vs 6.9%, p = 0.195). After multivariable adjustment, only female sex (odds ratio [OR] 1.44, p <0.001), higher patient age (OR 1.01/year, p = 0.002), and lower height (OR 0.98/cm, p = 0.004) independently predicted transradial access failure. In conclusion, female sex, higher age, and smaller height independently predict transradial access failure in coronary angiography and intervention. Failure rate in ST-elevation myocardial infarction is not significantly increased.
EVALuna2:33605

Prognostication of post-infarct chronic heart failure: Superiority of clinical assessment vs. cardiopulmonary and left ventricular function analysis - Nixdorff, Uwe; Drees, Michael; von Bardeleben, Stephan; Mohr-Kahaly, Susanne; Klinghammer, Lutz (International Journal of Cardiology, 2009)
Background: Prognostication of congestive heart failure post-myocardial infarction (MI) is important for decision making. We sought of a head-to-head comparison between the prognostic implication of clinical, cardiopulmonary, and left ventricular (LV) function assessment. Methods: Retrospectively, 100 consecutive post-MI patients (MI history 1418 ± 1668 days ago) were stratified by NYHA functional classification system, cardiopulmonary exercise testing (CPX) [oxygen consumption at maximal exercise (VO2max) and at the anaerobic threshold (VO2AT) resulting in the Weber classification], and LV function analysis by M-mode and two-dimensional echocardiography [LV end-diastolic and -systolic diameter index (LVDDI and LVSDI), shortening fraction (%D), and LV end-diastolic and -systolic volume index (EDVI and ESVI), LV ejection fraction (EF)]. Patients were controlled by phone call 1470 ± 607 days later. Results: There was only a modest correlation between NYHA and Weber classes (r = 0.402) and no correlation between VO2max and ESVI (r = 0.080) nor between NYHA and ESVI (r = 0.174). Several parameters (ESVI, LVDDI, LVSDI, %D) could discriminate NYHA classes to a higher significance (p = 0.05; 0.0008; 0.0002; 0.04) than the Weber classes (n.s.; p = 0.03; n.s.; n.s.). The following parameters could significantly differentiate quartiles in a log-rank analysis (Kaplan-Meier survival curves): NYHA classes (p = 0.0001), Weber classes (p = 0.069), EDVI (p = 0.004), ESVI (p = 0.0001), EF (p = 0.002), LVDDI (p = 0.002), LVSDI (p < 0.001) and %D (p < 0.001). Multivariate analysis isolated the following three parameters implying decreasing, independent prognostic information: NYHA classes (p = 0.001), ESVI (p = 0.003), and Weber classes (p = 0.040). Conclusions: In post-MI patients the thorough clinical assessment according the NYHA functional classification system implies higher prognostic information than more objective measures. This should be considered especially in primary care and should lessen the dependence on costly and expertise-dependent technical investigations. © 2007 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Cardiopulmonary exercise test; Congestive heart failure; Echocardiography; Myocardial infarction; NYHA; Prognosis

Randomized trial of acupuncture to lower blood pressure - Klinghammer, Lutz; et al. (Circulation, 2007)
Keywords: Hypertension; Life style; Risk factors

Red blood cell omega-3 fatty acids and the risk of ventricular arrhythmias in patients with heart failure - Wilhelm, Matthias; Tobias, Rueth; Asskali, Fatima; Kraehner, Robert; Kuly, Simone; Klinghammer, Lutz; Böhles, Hans Josef; Daniel, Werner (American Heart Journal, 2008)

Relation of functional echocardiographic parameters to infarct scar transmurality by magnetic resonance imaging - Rost, Christian; Rost, Marie-Charlotte; Breithardt, Ole A.; Schmid, Michael; Klinghammer, Lutz; Stumpf, Christian; Daniel, Werner; Flachskampf, Frank A. (Journal of the American Society of Echocardiography, 2014)
Identification of viable but dysfunctional myocardium after myocardial infarction is important for management, including the decision for revascularization. Assessment of infarct transmurality (TRM) by late contrast enhancement on magnetic resonance imaging (MRI) is frequently used for this task but has several limitations, particularly its availability. The goal of this study was to compare the value of several simple echocardiographic parameters measured at rest at the bedside for the identification of three degrees of infarct TRM, with contrast-enhanced MRI as the gold standard.In a prospective, single-center study, 41 patients (33 men; mean age, 62 ± 10 years; 32 with ST-segment elevation infarctions) underwent resting echocardiography and contrast-enhanced MRI <5 days after infarction. Wall motion score, preejection velocity by tissue Doppler, and longitudinal, circumferential, and radial peak systolic strain by speckle-tracking-based strain imaging were assessed, and the findings were compared with infarct TRM stratified by contrast-enhanced MRI (no scar, 0% TRM; nontransmural scar, 1%-50% TRM; and transmural scar, 51%-100% TRM).Four hundred segments showed no scar, 125 showed nontransmural scar, and 213 showed transmural scar on contrast-enhanced MRI. The sensitivity and specificity of visual wall motion scoring to detect any scar versus no scar were 71% and 81%, respectively, similar to values for circumferential strain (sensitivity and specificity both 81% with a cutoff of -14.5%). Longitudinal and radial strain performed less well, and the presence of preejection velocity performed distinctly worse (45% and 90%, respectively). The sensitivity and specificity for identifying nontransmural versus transmural infarction was better for circumferential strain (78% and 75%, respectively, with a cutoff of -10.5%) than for the other strain types, preejection velocity (52% and 67%, respectively), or visual wall motion scoring (50% and 81%, respectively, for a score > 2).Visual wall motion analysis alone is able to detect infarcted myocardium but cannot differentiate sufficiently between transmural and nontransmural infarction. This is best achieved at the bedside using speckle-tracking-based circumferential strain.
EVALuna2:11951

Response to letter regarding article, "Randomized trial of acupuncture to lower blood pressure" [2] - Flachskampf, Frank A.; Wortmann, Alois; Klinghammer, Lutz; Daniel, Werner; Gallasch, Joachim; Pflederer, Wolfgang; Gefeller, Olaf; Pfahlberg, Annette Bettina; Gan, Junxue; Mao, Juntong (Circulation, 2008)

Risk stratification by analysis of QT dispersion and late potentials in the electrocardiogram and biplanar magnetocardiogram in patients with coronary heart disease Risikostratifikation durch Analyse von QT-Dispersion und Spätpotentialen im Elektrokardiogramm und biplanen Magnetokardiogramm bei Patienten mit KHK. - Klinghammer, Lutz; et al. (Biomedizinische Technik, 1998)

Sequential changes in myocardial function after valve replacement for aortic stenosis by speckle tracking echocardiography - Rost, Christian; Korder, S.; Wasmeier, G.; Wu, M.; Klinghammer, Lutz; Flachskampf, F. A.; Daniel, Werner; Voigt, J. U. (European Journal of Echocardiography, 2010)
Aims Regional myocardial function may change differently in different pathology. Speckle tracking echocardiography (STE) was applied to evaluate longitudinal, radial, and circumferential function in patients with aortic stenosis (AS) before, within 1 week, and 6 months after aortic valve replacement (AVR). Methods and results In 40 consecutive patients with severe AS, we acquired apical four-, three-, and two-chamber views and standard short-axis view pre- and post-AVR and after 6 months. Longitudinal, radial, and circumferential (LS, RS, and CS) were calculated by commercial STE software. Further, we analysed diastolic myocardial function by measuring E/e′ ratio. With AVR, valve area increased and remained stable at 6 months follow-up. Left ventricular mass was unchanged 1 week after AVR (270 ± 58 g vs. 267 ± 58 g, n.s.) but decreased significantly during the next 6 months (219 ± 50 g, P < 0.05). Left ventricular ejection fraction remained unchanged. Strain values did not change significantly within 1 week after AVR but increased significantly after 6 months (LS by 16, RS by 21, and CS by 28 of baseline values). E/e′ ratio was highly augmented before AVR (26.1 ± 12.5) and decreased significantly 6 months after AVR (15.9 ± 5.9). Conclusion Myocardial function significantly recovers after replacing the stenosed aortic valve. However, there is a considerable difference between the response of longitudinal, radial, and circumferential function. Our data suggest that echocardiographic assessment of regional function is feasible and of potential clinical importance. © The Author 2010.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Aortic stenosis; Aortic valve replacement; Diastolic dysfunction; Echocardiography; Strain

Serum levels of the Th1 chemoattractant interferon-gamma-inducible protein (IP) 10 are elevated in patients with essential hypertension - Stumpf, Christian; Auer, Claudia; Yilmaz, Atilla; Lewczuk, Piotr; Klinghammer, Lutz; Schneider, Markus; Daniel, Werner; Schmieder, Roland; Garlichs, Christoph (Hypertension Research, 2011)
Growing evidence shows that inflammation has a pivotal role in the pathophysiology of essential hypertension (EH). Although it has been acknowledged that target organ damage involves an inflammatory response, most work has focused on the role of macrophages, but T lymphocytes have recently become the center of interest. The goal of our study was to evaluate the role of T-cell-specific cytokines in the pathogenesis of EH. The study examined 39 patients with EH (57.7±6.8 years, systolic blood pressure (SBP) 157.5±11.8 mm Hg, diastolic blood pressure 92.2±12.9 mm Hg, mean arterial pressure 113.9±12.6 mm Hg) and 30 healthy, normotensive controls (55.2±4.9 years). Blood was drawn from a peripheral vein, and serum levels of interferon-inducible protein (IP)-10 and interleukins (IL)-4,-7 and-13 were measured by a multiplexing assay. Hypertensive patients had significantly higher levels of IP-10, IL-4, IL-7 and IL-13 than control subjects. When the patients were classified into tertiles according to their serum IP-10 levels (T1: 41.2-9±4.1 pg ml-1; T2: 103.4-1±62.5 pg ml 1; T3: 171.7-443.5 pgml 1), the patients classified into the highest tertile also had the highest blood pressure. In a correlation analysis, plasma IP-10 concentration was significantly associated with SBP (r0.59, P<0.001). Furthermore, hypertensives with microalbuminuria, an early sign of hypertensive target organ damage, had the highest IP-10 levels. A stepwise multivariate regression analysis revealed IP-10 as the strongest independent predictor of SBP (P<0.01). In conclusion, our study provides new insights into the pathophysiological mechanisms in EH linking inflammation and IP-10. However, these preliminary results need to be confirmed in larger trials. © 2011 The Japanese Society of Hypertension All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: cytokines; inflammation; IP-10; microalbuminuria; T-cells

Short-term prognosis of contemporary interventional therapy of ST-elevation myocardial infarction: Does gender matter? - Zimmermann, Stefan; Ruthrof, Susanne; Nowak, Kathrin; Alff, Anna; Klinghammer, Lutz; Schneider, Reinhard; Ludwig, Josef; Pfahlberg, Annette; Daniel, Werner; Flachskampf, Frank A. (Clinical Research in Cardiology, 2009)
Background: A higher mortality risk for women with acute ST-elevation myocardial infarction (STEMI) has been a common finding in the past, even after acute percutaneous coronary intervention (PCI). We set out to analyze whether there are gender differences in real-world contemporary treatment and outcomes of STEMI. Patients and methods: A retrospective analysis of all consecutive patients with STEMI and acute coronary angiography with the intention of performing a PCI at our center 6/1999-6/2006 was carried out (n = 566). Data were examined for gender-specific differences regarding patients' characteristics, referral patterns, timing of acute symptoms, angiographic findings, procedural details, and adverse events at 30 days after PCI. Results: Women (n = 161) were on average 8 years older than men (n = 405), had higher co-morbidity, were more often transported to the hospital by ambulance and presented less often to the emergency room on their own (4.2% vs. 12.6% in men, P = 0.02). The pre-hospital delay from symptom onset to admission was significantly longer for women (median 185 vs. 135 min, P < 0.02). There was no gender difference in time from admission to PCI (median 46 min vs. 48 min, P = 0.42). Both genders received PCI with similar frequency (88.8% vs. 92.4%, P = 0.19), with similar success rates (83.2% vs. 85.3%, P = 0.68). Thirty-day overall mortality for women was not significantly higher than for men (8.7% vs. 7.2%, P = 0.6). Re-infarction or stroke within 30 days were rare for both genders without gender-specific differences whereas bleeding necessitating blood replacement was significantly more frequent in women (16.8% vs. 5.9%, P < 0.001). In multivariate analysis, female gender was not independently associated with a higher risk of 30-day mortality (OR 0.964, P = 0.93). Conclusions: Women underwent PCI therapy for STEMI with the same frequency and the same angiographic success as men. Despite their more advanced age and the higher prevalence of co-morbidities, they did not have a significantly higher 30-day mortality rate than men. Female gender was not an independent risk factor of 30-day mortality. Longer pre-hospital delays before hospital admission in women indicate that awareness of risk from coronary artery disease should be further raised in women. © 2009 Springer-Verlag.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Gender differences; Outcomes; Primary coronary intervention; ST-elevation myocardial infarction

Simultaneous hemodialysis during coronary angiography fails to prevent radiocontrast-induced nephropathy in chronic renal failure - Klinghammer, Lutz; et al. (Clinical Nephrology, 2003)
Keywords: Radiocontrast-induced nephropathy; Simultaneous hemodialysis; Chronic renal failure

Successful cardiopulmonary resuscitation after cardiac arrest as a sepsis-like-syndrome - Bal, Zeynep; Klinghammer, Lutz; Achenbach, Stephan; Schneider, R. (2016)
EVALuna2:33687

The proinflammatory effect of C-reactive protein on human endothelial cells depends on the Fc?RIIa genotype - Raaz-Schrauder, Dorette; Ekici, Arif Bülent; Klinghammer, Lutz; Stumpf, Christian; Achenbach, Stephan; Herrmann, Martin; Reis, André; Garlichs, Christoph (Thrombosis Research, 2014)
The stimulatory effects of CRP (C-reactive protein) on endothelial cells are mainly mediated via Fc?RIIa. This receptor exists in two different allotypes bearing either arginine (R131) or histidine (H131) at the extracellular amino acid position 131 of the mature protein, but only Fc?RIIa-R131 displays high avidity for CRP. This study investigated the role of the Fc?RIIa genotype in CRP-stimulated endothelial cells.We tested the effects of CRP on expression of the adhesion molecules ICAM-1, VCAM-1, and E-selectin, as well as the endothelial release of pro-inflammatory molecules as a function of the Fc?RIIa-genotype (Fc?RIIa-H/H131, Fc?RIIa-H/R131, Fc?RIIa-R/R131) in HUVEC (Human Umbilical Vein Endothelial Cells). HUVEC were grouped according to their Fc?RIIa status by genotyping with an allele specific nested-PCR. The expression of ICAM-1, VCAM-1, and E-selectin on HUVEC was detected by flow cytometry. The release of soluble markers (sCD40L, IL-6, IL-8, MCP-1, tPA, sP-selectin, and sVCAM-1) was measured using a multiplex assay for flow cytometry.CRP-stimulated expression of ICAM-1 and E-selectin was dependent on the specific Fc?RIIa-genotype, with most pronounced induction in HUVEC with the Fc?RIIa-R/R genotype, followed by H/R and H/H. In accordance with this finding, the supernatants of stimulated HUVEC with the R/R genotype showed significantly higher levels of tPA, MCP-1, and IL-6. Our data show that CRP stimulates the expression of adhesion molecules and the release of soluble markers by HUVEC as a function of the Fc?RIIa-genotype. These findings could be relevant in the context of risk stratification in patients with cardiovascular disease.
EVALuna2:9209

The trigonometric regressive spectral analysis - A method for mapping of beat-to-beat recorded cardiovascular parameters on to frequency domain in comparison with Fourier transformation - Rüdiger, Heinz; Klinghammer, Lutz; Scheuch, Klaus (Computer Methods and Programs in Biomedicine, 1998)
Heart rate and peripheral blood pressure as physiological recorded vegetative parameters are very often rhythmically investigated with the Fourier Transformation (FT). In contrast to the original use of FT these parameters are still stochastic with overlaying rhythmical structures. The R-R intervals as independent variables of time are not equidistant. The mathematical structure for the spectral decomposition is critically analyzed. The purpose of this article is the presentation of a mathematical method, considering both the statistical and rhythmical features of such time series. On the basis of trigonometric regressions, this method is presented to eliminate the equidistance problems, arising with the usage of FT, by a new mathematical approach. This method computes more precisely the spectral power especially in the VLF range (0.003-0.04 Hz) than FT, because this method of trigonometric regression does not perform a frequency quantization. This method has been used and successfully tested for the analysis of peripheral blood pressure and R-R intervals including an effective reduction of input data.
Created from Fastlane, Scopus look-up
Keywords: Blood pressure variability; Fourier transformation; Heart rate variability; Point events; Trigonometric regressive spectral analysis

Transesophageal demonstration of a coronary fistula with associated infective endocarditis Transosophageale darstellung einer koronarfistel bei gleichzeitiger endocarditis lenta - Klinghammer, Lutz; et al. (Z KARDIOL, 1999)
Keywords: Endocarditis; Coronary fistula; Transesophageal echocardiography

Transradial approach for coronary angioplasty in the setting of acute myocardial infarction: A dual-center registry - Klinghammer, Lutz; et al. (Catheterization and Cardiovascular Interventions, 2002)
Keywords: Abciximab; Radial artery; Rescue angioplasty; Acute myocardial infarction; Primary angioplasty; Thrombolysis

Usefulness of magnetocardiography for the investigation of fetal arrhythmias - Klinghammer, Lutz; et al. (American Journal of Cardiology, 2001)